Dividend Policy and Firm Performance of Listed Consumer Goods Companies in Nigeria Exchange Group - Olaoye, Clement Olatunji; Olaniyan, Niyi Oladipo (Acta Universitatis Danubius. Œconomica, 2022)
The study examined the effect of dividend policy on firm performance of listed consumer goods companies in Nigeria exchange group, it specially examined the effect of dividend payout on return on asset, it examined the effect of dividend payout on retained earnings, as well it examined the effect of dividend payout on debt on equity of listed consumer goods companies in Nigeria. The study was anchored on social contract. Secondary sources of information were employed to extract useful information from the Audited Annual Reports of the eight (8) consumer goods firms sampled for the investigation for the periods 2010-2020. Panel data least square multiple regression was used to test the hypothesis. Findings reveal that dividend payout have positive and significant relationship with return on asset, required retained earnings (β= 0.0321, p-value = 0.0037, β= 0.3425, p-value = 0.005, and dividend payout has a negative and statistically significant effect on debt on equity with (β= -0.7286, p-value = 0.15). The study therefore recommends among others that the management of consumer goods companies should make it a priority to increase the number of dividends paid out to their customers' stocks in order to boost the companies' overall profitability. This is necessary due to the fact that there is a robustly positive correlation between dividend payout and return on assets.